PENGARUH PRODUCT QUALITY DAN SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN (STUDI PADA KFC GIANT PANAM PEKANBARU) - Fanani, Anwar; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The problem in this study is the percentage of achievement of sales targets has decreased, this is thought to be influenced by consumer dissatisfaction with product quality and service quality. The purpose of this study was to determine product quality and service quality on customer satisfaction in KFC Giant Panam Pekanbaru. The population in this study is KFC Giant Panam Pekanbaru consumers. The sample taken is based on the method using the incidental sampling guidelines in sugiono on the third point, amounting to 100 respondents. The data in this study used a survey method through a questionnaire filled out by consumers. Data obtained from the result of the questionnaire and then processed to then be tested with statistics through the SPSS23 program. Hypothesis testing usus simple linear analysis methods and multiple linear analysis with the results showing that product quality and service quality have a positive and significant effect on customer satisfaction on KFC Giant Panam Pekanbaru. With the calculation of the coefficient of determination (R²) of simple product quality to customer satisfaction obtained an R square value of 0,642 or 64,2% and service quality to customer satisfaction obtained an R square value of 0,339 or 33,9% and a calculation of determination (R²) of multiple product quality and service quality on customer satisfaction obtained R square value of 0,503 or 50,3%, this shows that product quality and service quality have and effect of 50,3% on customer satisfaction on KFC Giant Panam Pekanbaru, while the remaining 49,7% is influenced by other variables not examined in this study. Keywords: Product Quality, Service Quality, and Customer satisfaction